2020
DOI: 10.1111/jir.12735
|View full text |Cite
|
Sign up to set email alerts
|

Trends and predictions for survival and mortality in individuals with Down syndrome in Brazil: A 21‐year analysis

Abstract: Background Regional heterogeneities and sociodemographic characteristics affect mortality and population survival in Brazil. However, for individuals with Down syndrome (DS) this information remains unknown. In this study, we analysed survival and mortality rates among DS individuals in the five Brazilian geographic regions. In addition, we investigated whether there is an association between mortality and sociodemographic factors across administrative regions. Methods Data between 1996 and 2016, comprising 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Christianson et al (2006) reported that 65% of the infants and children with DS had died by the age of two in South Africa in the early and mid-1990s. Coinciding with the report in Brazil that children were more susceptible to death (de Campos Gomes et al, 2020), the majority of deaths occurred in the children less than 5 years old in different SDI region except high SDI region. Prioritizing a reduction in deaths of newborns and children is one of the seventeen Sustainable Development Goals (Nations, 2014).…”
Section: Charleton Et Al Once Formulated Almost 44 Particular Medicalsupporting
confidence: 53%
See 2 more Smart Citations
“…Christianson et al (2006) reported that 65% of the infants and children with DS had died by the age of two in South Africa in the early and mid-1990s. Coinciding with the report in Brazil that children were more susceptible to death (de Campos Gomes et al, 2020), the majority of deaths occurred in the children less than 5 years old in different SDI region except high SDI region. Prioritizing a reduction in deaths of newborns and children is one of the seventeen Sustainable Development Goals (Nations, 2014).…”
Section: Charleton Et Al Once Formulated Almost 44 Particular Medicalsupporting
confidence: 53%
“…Both age-standardized DALYs and ASDR were negatively correlated with SDI, indicating that difference might be partly attributed to social and economic factors. Analogously, many studies indicated that sociodemographic characteristics impacted the survival and the risk of mortality for patients with DS (Fiscella et al, 2000;de Campos Gomes et al, 2020). According to the literature, the most common reason of death in childhood and adulthood remained as respiratory infection (Bull, 2020); dementia was the direct reason of death in 70% of dead older people with DS (McGlinchey et al, 2020).…”
Section: Charleton Et Al Once Formulated Almost 44 Particular Medicalmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, blacks have a higher risk than whites [48,49], which is coherent with the ndings of our study. However, only a few reports of the association between yellows and disease are available in the literature [50,51]. The effect of the level of yellows on the survival of LGGs was similar according to survival models.…”
Section: According To Our Nomograms Age At Diagnosis Was Con Rmed Asmentioning
confidence: 89%
“…The lower prevalence in Brazil might be because of the difference in the maternal age profile ( 1 ). Nevertheless, death among persons with Down syndrome in Brazil has increased in recent years, particularly among children ( 2 ). Socioeconomic and regional differences in the quality of and access to healthcare, particularly in the North and Northeast regions, might explain increased death rates ( 2 , 3 ).…”
mentioning
confidence: 99%